Association of Serum Lipids with Outcomes in Hispanic Hemodialysis Patients of the West vs. East Coasts of the United States - Moradi, Hamid (Am J Nephrol, 2015)
BACKGROUND: Paradoxical associations exist between serum lipid levels and mortality in patients on maintenance hemodialysis (MHD) including those of Hispanic origin. However, there are significant racial and ethnic variations in patients of “Hispanic” background. We hypothesized that clinically meaningful differences exist in association of lipids and survival in Hispanic MHD patients on the West versus East Coast. METHODS: We examined the survival impact of serum lipids in a 2-year cohort of 15,109 MHD patients of Hispanic origin being treated in California, Texas, representing the West versus New York, New Jersey and Florida representing the East Coast, using Cox models with various degrees of adjustments. RESULTS: Association of serum total and HDL cholesterol with mortality follows a U-shaped pattern in Hispanic patients residing in the West. This is in contrast to Hispanic patients in the East Coast whose survival seems to improve with increasing total and HDL cholesterol levels. Elevated serum LDL levels in Hispanic patients on the West Coast are associated with a significant increase in mortality, while this association is not observed in patients residing on the East Coast. CONCLUSIONS: Substantial differences exist in association of serum lipids with mortality in MHD patients of Hispanic background depending on whether they reside on the West or East Coast of the United States. These geographical variances most likely reflect ethnic, racial and genetic distinctions which are usually ignored. Future studies should take into account these critical variations in a population of patients who make up a significant portion of our society.